Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/ajmg.b.31071
|View full text |Cite
|
Sign up to set email alerts
|

Severe mental retardation, seizures, and hypotonia due to deletions of MEF2C

Abstract: We present four patients, in whom we identified overlapping deletions in 5q14.3 involving MEF2C using a clinical oligonucleotide array comparative genomic hybridization (CGH) chromosomal microarray analysis (CMA). In case 1, CMA revealed an approximately 140 kb deletion encompassing the first three exons of MEF2C in a 3-year-old patient with severe psychomotor retardation, periodic tremor, and an abnormal motor pattern with mirror movement of the upper limbs observed during infancy, hypotonia, abnormal EEG, ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
2

Year Published

2011
2011
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 36 publications
3
104
2
Order By: Relevance
“…Since 2009, six authors have reported on 5q14.3q15 microdeletions and the associated clinical findings [Cardoso et al, 2009;Engels et al, 2009;Le Meur et al, 2010;Nowakowska et al, 2010;Novara et al, 2010;Zweier et al, 2010]. From these reports, a common syndrome of developmental delay/mental retardation, hypotonia, absent speech, mild facial dysmorphology, seizures, and brain anomalies emerges.…”
Section: Discussion Mef2cmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2009, six authors have reported on 5q14.3q15 microdeletions and the associated clinical findings [Cardoso et al, 2009;Engels et al, 2009;Le Meur et al, 2010;Nowakowska et al, 2010;Novara et al, 2010;Zweier et al, 2010]. From these reports, a common syndrome of developmental delay/mental retardation, hypotonia, absent speech, mild facial dysmorphology, seizures, and brain anomalies emerges.…”
Section: Discussion Mef2cmentioning
confidence: 99%
“…This phenotype has been described in six reports encompassing 19 patients with a 5q14.3q15 microdeletion ( Fig. 1) [Cardoso et al, 2009;Engels et al, 2009;Le Meur et al, 2010;Novara et al, 2010;Nowakowska et al, 2010;Zweier et al, 2010]. An emerging consensus points to haploinsufficiency of MEF2C, a member of the myocyte enhancer factor-2 (MEF2) transcription factor family [Potthoff et al, 2007], as the genetic etiology underlying this complex phenotype.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Mutations in human MEF2C are strongly associated with neuronal disorders, including seizures, mental retardation and epilepsy (Le Meur et al, 2010;Novara et al, 2010;Nowakowska et al, 2010), demonstrating the important role for MEF2C in the development of neuronal lineages in humans. Mutations in human SOX10 often cause a severe form of Waardenburg syndrome (Type IV, also known as Waardenburg-Hirschsprung disease), which involves aganglionic colon and severe pigmentation defects (Parisi and Kapur, 2000;Pingault et al, 1998;Pingault et al, 2010).…”
Section: Mef2c As a Candidate Gene Involved In Neural Crest Disordersmentioning
confidence: 99%
“…MEF2C activity is modulated by post-translational modifications in response to cytoplasmic signals including calcium (37). Mutations in human MEF2C are associated with neurological disorders including mental retardation and seizures (43,44).…”
mentioning
confidence: 99%